PERHITUNGAN VALUE AT RISK PORTOFOLIO SAHAM MENGGUNAKAN METODE SIMULASI MONTE CARLO - Adilla Chandra; Johannes Kho; Musraini M (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
This article discusses the calculation of Value at Risk (VaR) for stock portfolio usingMonte Carlo simulation. The standard deviation of return data of multiple stock andportfolio are normally distributed and used in the calculation of VaR. Monte Carlomethod is applied to simulate a new return value of stock and portfolio by generating arandom numbers based on the characteristics of the data, which is then used to estimatea VaR. The calculation of VaR at portfolio uses two assets which are Semen Indonesia (Persero) Tbk (SMGR.JK) and PT. Unilever Indonesia Tbk (UNVR.JK).